In-vitro antioxidant and antibacterial activities of tegeran wood (Cudrania javanensisTrécul) extracts [Aktivitas antioksidan dan antibakteri ekstrak kayu tegeran secara in-vitro(Cudrania javanensisTrécul)] - Cici Darsih; Anastasia Wheni Indrianingsih; Anjar Windarsih; Khoirun Nisa; Vita Taufika Rosyida; Sri Handayani; Martha Purnami Wulanjati; Nurina Indirayati; Dwi Ratih (Jurnal Riset Industri Hasil Hutan, 2020)
Cudrania javanensis generally used as natural dyes in Indonesia, but limitedis known about its biological activities. The study aimed to assess in vitro antioxidant and antibacterial activities of C. javanensis crude extracts. The antioxidant properties of crude extracts were determined by the DPPH free radical and ABTS method. Methanol and water extracts were also evaluated for their antimicrobial activities toward strain of Gram positivebacteria (Staphylococcus aureus) and Gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa) by the agar well diffusion method. The results indicated that C. javanensis wood methanol extract exhibited good antioxidant activity than water extract, which against DPPH radical with IC50of 12.23±1.43 μg/mL, andscavenging to ABTS radical about 964.69±15.05 mg trolox equivalent/g at 0.025 mg/mL, respectively. However, both of extracts did not possess activity toward antibacterial assay. This study indicated that methanol and water extracts from C. javanensis wood could be used as natural antioxidant resources.